Clinical, laboratory and ultrasonographic risk factors for uterine artery arteriosclerosis: Insights for uterus transplantation. Issue 2 (23rd November 2022) - Raimondo, Diego; Raffone, Antonio; Renzulli, Federica; Raimondo, Ivano; Raspollini, Arianna; Rovero, Giulia; Franceschini, Camilla; Maletta, Manuela; Carbone, Luigi; Lenzi, Jacopo; Mollo, Antonio; Seracchioli, Renato; et al.
Abstract: Objective: To assess uterine artery arteriosclerosis prevalence in women undergoing total hysterectomy for benign diseases, and any associations between clinical, laboratory, and ultrasound factors and uterine artery arteriosclerosis occurrence. Methods: A single center, observational, prospective, cohort study was performed enrolling all symptomatic patients scheduled for total hysterectomy from May to December 2021. Our outcomes were: uterine artery arteriosclerosis prevalence and the difference in clinical, laboratory, and ultrasonographic factors between patients with and without uterine artery arteriosclerosis. Results: Forty women were included. Uterine artery arteriosclerosis prevalence was 70%. Body mass index (BMI) ( P  = 0.04) and triglycerides ( P  = 0.04) were significantly higher in patients with uterine artery arteriosclerosis than in patients without; while high‐density lipoprotein (HDL) ( P  = 0.02) was significantly lower. Uterine arteries with arteriosclerosis showed higher peak systolic velocity (PSV) values compared with vessels without arteriosclerosis ( P  = 0.05). Conclusions: Uterine artery arteriosclerosis shows a high prevalence in women undergoing total hysterectomy for benign diseases. Higher BMI, serum triglycerides, and PSV, and lower serum HDL appear as risk factors for uterine artery arteriosclerosis. Synopsis: Uterine artery arteriosclerosis has a high prevalence in women undergoing hysterectomy. Dyslipidemia and higher BMI and peak systolic velocity appear as risk factors.